WRITING PROCESS MODELS AND THEIR INFLUENCE ON FOREIGN LANGUAGE STUDENTS’ WRITING PRODUCTS - Ilhama Rahimova (European Research Materials, 2023)
This article looks at the models of writing in native language and the second language. The process approach to teaching with its emphasis on the writing process, meaning composing and multiple drafts is appropriate only for the second language learners. This is especially evident if they receive substantial support from their teachers’ side, and are proficient enough in the field of the language being studied to transfer their ideas into writing.